Hyacinth invasion in Nigeria - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The Nigerian government has set up a special committee to deal with the severe infestation of water hyacinth. In the large creek and lagoon complexes of Lagos and Ondo States the weeds are cutting off access to communities which depend on water...